Perineal Massage on the Prevention of Perineal Lacerations Among Maternity Mothers : A Literature Review - Yulizawati; Hardisman; Firdawati; Utami, Riezka Putri; Rita, Rauza Sukma; Lisa, Ulfa Farrah; Iffah, Uliy (Women, Midwives and Midwifery, 2024)
Background: Childbirth is a physiological process, which is ended by removal of the fetus, placenta, and membrane from the uterus in full-term pregnancy without action and complications. During the childbirth there are complications that can cause death, one of which is the case of perineal lacerations. Perineal massage is an action that can be done to prevent the occurrence of perineal lacerations in maternity mothers.   Purpose: This study aims to determine perineal massage on the prevention of perineal lacerations in maternity mothers. Methods: This research method was a literature review study. Journal searches were carried out by applying online database such as Sciencedirect, PubMed, Scopus, Google Scholar, Semantic Scholar, and Portal Garuda. Articles were selected based on inclusion and exclusion criteria. Results: The analysis was carried out on 18 research articles. It was found that perieneal massage can cause vasodilation of blood vessels so that blood flow to the perineum increases so that the perineal area becomes more elastic. The application of perineal massage is able and effective in preventing and reducing the incidence of perineal lacerations in maternity mothers. Conclusion: The influence of perineal massage is useful in the prevention of perineal lacerations in maternity mothers.